2017
DOI: 10.1136/neurintsurg-2017-013110
|View full text |Cite
|
Sign up to set email alerts
|

Timing of complications during and after elective endovascular intracranial aneurysm coiling

Abstract: This study demonstrates that coiling-related complications of elective endovascular coiling tend to occur either intraoperatively or are detected shortly after reversal of anesthesia. Further investigation with a larger cohort may help to guide important preoperative communication with patients and identify a select group of patients who may not necessarily require prolonged admission to hospital for observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Early experience with eCLIPs provided a learning curve and limited the recommendation to implant the eCLIPs in BT and CT aneurysms only 7 20. Procedural time, as well as procedural complexity, has demonstrated a strong association with the occurrence of procedure related complications 21 22. In this small series, it did not result in more safety events compared with other recent studies14 17–19; nevertheless, shortening total procedure times is an important objective.…”
Section: Discussionmentioning
confidence: 78%
“…Early experience with eCLIPs provided a learning curve and limited the recommendation to implant the eCLIPs in BT and CT aneurysms only 7 20. Procedural time, as well as procedural complexity, has demonstrated a strong association with the occurrence of procedure related complications 21 22. In this small series, it did not result in more safety events compared with other recent studies14 17–19; nevertheless, shortening total procedure times is an important objective.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, our results were similar after a 30-day washout period that ensured that only new ischemic stroke events were captured in the analysis. Fourth, while we did not obtain information on aneurysm treatment procedures such as clipping or endovascular coiling; this likely did not influence our findings particularly because these procedures tend to increase the risk of stroke intraor perioperatively, and not long-term after the index SAH [32,33]. Information on medications often used for secondary stroke prevention such as antithrombotic, lipid lowering, and antihypertensive therapy were not available.…”
Section: Discussionmentioning
confidence: 98%
“…Critical care units are substantially more expensive than other hospital units, and their direct costs are rising [15,16]. Complications of EVT of UIAs are known but rare, making their indirect costs challenging to measure [17][18][19][20][21][22]. Hospital charges for EVT of UIAs often exceed those for surgical clipping [17].…”
Section: Discussionmentioning
confidence: 99%
“…Half of the complications that occurred <4 hours after intervention required treatment or resulted in permanent deficits, whereas those that occurred >12 hours after intervention were discharged home without deficits [21]. Furthermore, others have reported that 88% of complications occur within 24 hours of intervention [22]. In our study, the mean NCCU LOS was 1.07 days, and the admission to NCCU likely would not have hastened the detection of, reduced the morbidity associated with, or prevented the post-procedure complications.…”
Section: Discussionmentioning
confidence: 99%